APPLICATIONS OF CONVEX POLYGON AND KERNEL DENSITY ANALYSES TO MODEL THE HOME RANGES OF EQUATORIAL SPITTING COBRA Naja sputatrix (BOIE, 1827) IN GREEN AREAS OF UNIVERSITAS INDONESIA CAMPUS, WEST JAVA - Andriwibowo Andriwibowo; Adi Basukriadi; Erwin Nurdin (ZOO INDONESIA, 2022)
Naja sputatrix (Boie, 1827) or known as equatorial spitting cobra is one of venomous snake inhabiting wide green areas include Universitas Indonesia Campus. Currently the existence and conservation of cobra is threatened, then it is important to study cobra possible home ranges. This research is aiming to model the home range of equatorial spitting cobra in green areas of Universitas Indonesia Campus. The model was developed using the applications of Convex Polygon and Kernel Density. The Convex Polygon analysis shows that approximately 114.53 Ha or equals to 35.79% of green areas of Universitas Indonesia Campus was the home ranges of the cobra. While, based on the Kernel Density analysis, it confirms that up to 307.65 Ha or equals to 96.14% of green areas of Universitas Indonesia Campus were potentials as the home ranges of the cobra. Then it can be concluded that at least 30-90% of green areas of Universitas Indonesia Campus should be conserved to support the presences of N. sputatrix.